Use of semaglutide for aesthetic and weight loss purposes by non-diabetic individuals (Research, Society and Development, 2023)
Objective: To analyze the impact and factors that contribute to the use of semaglutide for purposes weight loss by non-diabetic individuals. Methods: The present study is an integrative literature review, through searches in PubMed, SciELO and VHL databases. Results: By performing the bibliographic search in the databases, different findings related to the slimming effects of semaglutide were evidenced, in a dose-dependent manner and according to the duration of treatment. In addition, it has been shown to be not only superior in reducing body weight compared to other antidiabetic drugs, but also cardioprotective, despite the commonly reported occurrence of gastrointestinal side effects such as nausea and vomiting. Final considerations: In this way, semaglutide appears as a therapeutic option that demonstrates a perspective of effectiveness and tolerability with higher rates than other drugs previously used for the treatment of obesity and chronic overweight.